Preliminary Study on Production Of 32P – Labeled Phosphate Chromic as A Material for Skin Patch - Wira Y. Rahman; Endang Sarmini; Herlina Herlina; Abidin Abidin; Triyanto Triyanto; Hambali Hambali; Sriyono Sriyono; Triani Widyaningrum (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Keloids are skin disorders or benign tumours that are due to abnormal wound healing in the binding tissue after a trauma, inflammation, surgical wounds, or burns. Low activity radioisotopes have shown to be effective in curing or eliminating keloids on the skin. One of these radioisotopes is phosphorus-32 (32P), a beta (β-) emitter with a half-life of 14.3 days. This radioisotope can also be developed for the treatment of keloid and skin tumours. Currently, keloid is treated by a conventional method e.g.by applying the bulk of 32P radioisotope directly on keloid area. However, this method is considered inefficient and less secure. The purpose of this research is to obtain a technology for preparing of 32P-labeled skin patch. The first step of this research is to produce 32P-labeled chromic phosphate (Cr32PO4) colloids, through condensation involving oxidation-reduction reaction. In this step, Cr (VI) is reduced to Cr (III) to form Cr32PO4 with particle size of <1 μm. These particles (Cr32PO4) are to expect to distribute evenly when mixed with silicon to form skin patch which will not decompose easily. Characterization of the prepared Cr32PO4colloids gave a yield of 97,8% with particle size of greater than > 1μm. Further study needs to be performed in due time in order to have Cr32PO4 colloids with a suitable particle size.Key words: keloid, chromic phosphate colloid, skin patch, condensation, oxidation-reduction reaction